Witreoretinopatia proliferacyjna – wybrane zagadnienia morfologii i patofizjologii - Laudańska-Olszewska, Iwona; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Based on the literature review the article presents state of the art knowledge on creation, structure and pathophysiology of membranes occurring in PVR. Additionally selected clinical risk factors are discussed.